A dynamic resource constrained project scheduling problem. (1st January 2013) - da Silva, André Renato Villela; Ochi, Luiz Satoru
In this paper, we present a variant of classical scheduling problems which deal with restricted resources. Unlike other models studied in the literature, the proposed model has no upper bound for the amount of available resources. The objective of this variant is to find a solution that maximises this amount at the end of the planning horizon. A hybrid evolutionary algorithm is proposed for this problem presenting very promising computational results.